2018
DOI: 10.3389/fonc.2018.00001
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Viruses and Breast Cancer: Mouse Mammary Tumor Virus (MMTV), Bovine Leukemia Virus (BLV), Human Papilloma Virus (HPV), and Epstein–Barr Virus (EBV)

Abstract: BackgroundAlthough the risk factors for breast cancer are well established, namely female gender, early menarche and late menopause plus the protective influence of early pregnancy, the underlying causes of breast cancer remain unknown. The development of substantial recent evidence indicates that a handful of viruses may have a role in breast cancer. These viruses are mouse mammary tumor virus (MMTV), bovine leukemia virus (BLV), human papilloma viruses (HPVs), and Epstein–Barr virus (EBV-also known as human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
206
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(214 citation statements)
references
References 180 publications
5
206
0
3
Order By: Relevance
“…According to the International Cancer Agency, infectious agents such as viruses are responsible for 15-20% of human cancers [4]. Previous studies have shown that papillomavirus [5], Epstein-Barr virus (EBV) [2], mouse mammary tumor virus (MMTV) [6,7], and bovine leukemia virus (BLV) [8] are associated with an increased risk of breast cancer. Moreover, several recent studies have suggested a possible relationship between Human Herpes Virus-8 (HHV-8) and breast cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Cancer Agency, infectious agents such as viruses are responsible for 15-20% of human cancers [4]. Previous studies have shown that papillomavirus [5], Epstein-Barr virus (EBV) [2], mouse mammary tumor virus (MMTV) [6,7], and bovine leukemia virus (BLV) [8] are associated with an increased risk of breast cancer. Moreover, several recent studies have suggested a possible relationship between Human Herpes Virus-8 (HHV-8) and breast cancer [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Sеvеral rіsk factors mаy bе а cаusе of brеast cаncеr, of thеsе factors vіrаl іnfеctіon [10].Onе of thе most common typеs of vіrus sprеаd іn thе world Еpstеіn Bаrr vіrus(ЕBV) [11]. Еpstеіn Bаrr vіrus whіch cаn bе а cаusе of brеast cаncеr [12,13]. The study showеd that brеast cancеr casеs, іt was іn thе advancеd stagеs that mеan dеlayеd dіagnosіs of brеast cancеr, Thіs findіng agrееs wіth a study donе by Alwan and hіs coworkеr [18] whom found that thе cаusе of brеаst cаncеr progrеssіon іs duе to thе fаct thаt thе low аnd mіddlе-іncomе countrіеs аmong thеsе countrіеs of Іrаq do not hаvе а strong cаpаcіty for costs to obtаіn mеdіcаl аttеntіon аnd also lack of knowlеdgе and awarеnеss rеgardіng brеast cancеr [18].…”
Section: Discussionmentioning
confidence: 99%
“…The most significant GO terms were obtained from Module 199, and were associated with defense against other organisms, such as viruses. Numerous studies have indicated that the mouse mammary tumor virus, bovine leukemia virus, human papillomavirus, and Epstein-Barr virus are associated with breast cancer (Amarante and Watanabe, 2009;Alibek et al, 2013;Lawson et al, 2018). As shown in Figure 4A, genes in this module exhibit larger PCC and LA values.…”
Section: Functional Analysis Of Cerna Modules In Breast Cancermentioning
confidence: 95%